Analisis Gangguan Static Frequency Converter (SFC) PLTG Gilimanuk - Saputra, Reza Adisetia; yasa, I Wayan Sugara; Adrama, I Nyoman Gede (Universitas Pendidikan Nasional, 2020)
The electricity system in Bali is supported by several generators, including PLTD / G Pesanggaran, PLTG Gilimanuk, PLTG Pemaron, Sea Cables and IPP Generators in meeting electricity needs in Bali, which can supply electricity needs at the greatest peak load of 940 MW. Along with the increasing various types of electricity consumers in Bali, the performance of each operation is demanded to be in prime condition.However, it does not rule out the disturbance will occur over time, among others, at the Gilimanuk PLTG, an SFC interruption with Card Processor Error Indication and, the Gilimanuk PLTG unit failed to start with an indication on the HMI SSD N. Alarm caused by damage to the 24VDC